Inter- and Intramolecular Cycloaddition Reactions of Ethenetricarboxylates with Styrenes and Halostyrenes - Yamazaki, Shoko; Wang, Zhichao; Iwata, Kentaro; Katayama, Khotaro; Sugiura, Hirotaka; Mikata, Yuji; Morimoto, Tsumoru; Ogawa, Akiya (Synthesis, 2020)
Inter- and intramolecular cycloaddition reactions of ethenetricarboxylates with styrenes and α-halostyrenes have been investigated. The reactions of ethenetricarboxylates with styrenes or α-bromostyrenes in the presence of SnCl4 or SnBr4 stereoselectively gave 2,4-cis-substituted cyclobutanes. The intramolecular cycloaddition reactions of a series of styrene-functionalized ethenetricarboxylate amides, including in situ generated derivatives, showed high diversity of reaction modes depending on the structures and substituents of the substrates. The regioselectivity and stereoselectivity of the reactions as well as reaction mechanisms were discussed based on the DFT calculations.
Keywords: cyclobutane; ethenetricarboxylate; styrene; intermolecular cycloaddition; intramolecular cycloaddition